Programmed cell death-1 and programmed cell death ligand-1 antibodies-induced dysthyroidism. Issue 5 (May 2018) - Jaafar, Jaafar; Fernandez, Eugenio; Alwan, Heba; Philippe, Jacques
Abstract : Background: Monoclonal antibodies blocking the programmed cell death-1 (PD-1) or its ligand (PD-L1) are a group of immune checkpoints inhibitors (ICIs) with proven antitumor efficacy. However, their use is complicated by immune-related adverse events (irAEs), including endocrine adverse events (eAEs). Purpose: We review the incidence, time to onset and resolution rate of dysthyroidism induced by PD-1/PD-L1 Ab, and the clinical, biological and radiological findings. We aim to discuss the potential mechanisms of PD-1/PD-L1 Ab-induced dysthyroidism, and to propose a management algorithm. Methods: We performed a literature search of available clinical trials regarding PD-1/PD-L1 Ab in the PubMed database. We selected all English language clinical trials that included at least 100 patients. We also present selected case series or reports, retrospective studies and reviews related to this issue. Findings: In patients treated with PD-1 Ab, hypothyroidism occurred in 2–10.1% and hyperthyroidism occurred in 0.9–7.8%. When thyroiditis was reported separately, it occurred in 0.34–2.6%. Higher rates were reported when PD-1 Ab were associated with other ICI or chemotherapy. The median time to onset of hyperthyroidism and hypothyroidism after PD-1 Ab initiation was 23–45 days and 2–3.5 months, respectively. Regarding PD-L1 Ab, hypothyroidism occurred in 0–10% and hyperthyroidism in 0.5–2% of treated patients. The average time to onset of dysthyroidism after PD-L1 Ab was variable and ranged from 1 day after treatment initiation to 31 months. Conclusion: Dysthyroidism occurs in up to 10% of patients treated with PD-1/PD-L1 Ab. Hypothyroidism and reversible destructive thyroiditis are the most frequent endocrine adverse events (eAE) in PD-1/PD-L1 treated patients. Immune and non-immune mechanisms are potentially involved, independently of the presence of thyroid antibodies.